Green marketing and omnichannel strategies on purchase decisions: The mediating role of disruptive marketing innovation - Novita Herawati; Irsal Fauzi (International Journal of Applied Finance and Business Studies, 2026)
This study aims to analyze the effect of green marketing and omnichannel on purchasing decisions with disruptive marketing innovation as a mediating variable in environmentally friendly batik MSMEs. This study uses a quantitative approach with a survey method targeting Zie Batik Semarang consumers who have purchased products online and offline. Primary data were collected through a five-point Likert scale questionnaire and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The results show that green marketing does not have a significant effect on purchase decisions. Omnichanel have a significant effect on purchase decision. Green marketing does not have a significant effect on disruptive marketing innovation. Omnichanel have a significant effect on disruptive marketing innovation. Disruptive marketing innovation have a significant effect on purchase decision. Disruptive marketing innovation is unable to mediate the effect of green marketing on purchase decisions. Disruptive marketing innovation is able to mediate the effect of omnichannel on purchase decisions. These findings indicate that the implementation of sustainable marketing strategies integrated with omnichannel systems and adaptive marketing innovations can increase consumer purchasing decisions in environmentally friendly batik SMEs. This study is expected to serve as a reference for SME players in designing relevant marketing strategies in the era of digital disruption.